CFD-DEM-based simulation and performance analysis of key parameters in pneumatic high- speed precision maize seed-metering device - Chen, Junzhi; Qi, Shaobo; Xu, Fudong; Jia, Pengcheng; Yuan, Zixin; Xi, Dejun; Xu, Hongyang; Wang, Jinwu (Frontiers in Plant Science, 2025)
To reduce seed loss, miss and multiple seeding in high-speed precision sowing, a pneumatic high-speed precision maize seed metering device was designed and analyzed in this study. Single-factor CFD simulations were conducted for the diameter of the seedling tray shaped holes and the inner diameter of the seed guide tube, respectively. Results showed that a hole diameter of 4.5 mm offered the best balance between suction efficiency and stability at different angular positions on the seed plate. Likewise, a seed guide tube inner diameter of 22 mm resulted in more uniform airflow and more consistent seed acceleration. A subsequent coupled CFD-DEM simulation was conducted, beginning with single-factor studies to identify a negative pressure range of -4 to -6 kPa that ensures reliable seed pickup and transport. Multi-factor simulations then incorporated positive pressure assistance in the seed guide tube. Bench tests at a forward velocity of 10 km/h confirmed that the best parameter combination was a negative pressure of -4 kPa and a positive pressure of 3 kPa, achieving a seed qualification rate of 96.48% and a coefficient of variation of 10.90%. The relative error between simulation and experimental results was within 5%, demonstrating excellent agreement and effective seeding uniformity.